2000
DOI: 10.1073/pnas.150104097
|View full text |Cite
|
Sign up to set email alerts
|

Induction of wild-type p53 activity in human cancer cells by ribozymes that repair mutant p53 transcripts

Abstract: Several groups have attempted to develop gene therapy strategies to treat cancer via introduction of the wild-type (wt) p53 cDNA into cancer cells. Unfortunately, these approaches do not result in regulated expression of the p53 gene and do not reduce expression of the mutant p53 that is overexpressed in cancerous cells. These shortcomings may greatly limit the utility of this gene replacement approach. We describe an alternative strategy with trans-splicing ribozymes that can simultaneously reduce mutant p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 31 publications
(37 reference statements)
0
78
0
3
Order By: Relevance
“…[124][125][126][127] In contrast, gene therapy to introduce wildtype p53 results in a reduction of MDR1 promoter expression. 128) In addition, various types of transcription factors have been suggested to be involved in MDR1 expression, such as EGR1, 129) NF-IL6 130) and NF-R2. 131) In rodents, effects of C/EBPb 132) and NF-kB 133) were also proposed.…”
Section: Factors Affecting Mdr1 Expressionmentioning
confidence: 99%
“…[124][125][126][127] In contrast, gene therapy to introduce wildtype p53 results in a reduction of MDR1 promoter expression. 128) In addition, various types of transcription factors have been suggested to be involved in MDR1 expression, such as EGR1, 129) NF-IL6 130) and NF-R2. 131) In rodents, effects of C/EBPb 132) and NF-kB 133) were also proposed.…”
Section: Factors Affecting Mdr1 Expressionmentioning
confidence: 99%
“…The consensus sequence that defines the 5Ј donor site, AG/GURAGU, is less extensive than the 3Ј splice elements (Moore et al 1999), and it has remained uncertain whether this site could be efficiently exploited to effect trans-splicing repair. Group I ribozymes have been used to perform trans-splicing reactions in vitro to repair globin mRNA in sickle cell anemia-derived erythroid precursor cells (Lan et al 1998), and trans-splicing ribozymes have also been used successfully to induce changes in p53 and chloride channels (Watanabe and Sullenger 2000;Rogers et al 2002) by a 3Ј replacement process; to our knowledge, there is no published report demonstrating that ribozymes are capable of repair in a 5Ј manner. Additionally, in trypanosomes (Van der Ploeg 1986) and Caenorhabditis elegans (Krause and Hirsh 1987), it has been demonstrated that RNAs are commonly modified by the addition of a splice leader on the 5Ј terminus by transsplicing.…”
Section: Introductionmentioning
confidence: 99%
“…By stably introducing a trans-dominant negative p53 into wildtype p53-expressing cells, Shuetz and co-workers (24) showed that down-regulation of wild-type p53 led to up-regulation of the endogenous MDR1 RNA and protein, consistent with the role of p53 in MDR1 repression. More recently, it has been shown that induction of wild-type p53 activity in human cancer cells using ribozymes that repair mutant p53 proteins results in reduced activity of the MDR1 promoter (25).…”
mentioning
confidence: 99%